Role of Ultrasound in the Diagnosis of Hepatocellular Carcinoma in Patients with Chronic Liver Disease - Sarkar, Samar C; Ali Biswas, Md Mamun; Amin, Mashah Binte; Yasmin, Tarana; Shanta, Kaniza Kabir; Faria, Shamanta (Journal of Enam Medical College, 2022)
Background: Hepatocellular carcinoma (HCC) is a common cancer in humans. Its mortality ranks third among human malignancies. Cirrhosis of liver is a major contributor to hepatocellular carcinoma, about in 80% of the affected individuals. Fine needle aspiration cytology (FNAC) of the liver which is a minimal invasive procedure is essential to sort out primary and secondary neoplasm of the liver. Objective: The aim of this cross-sectional study was to determine the accuracy of ultrasound for diagnosis of HCC in comparison with FNAC findings. Materials and Methods: This study was done in the Radiology & Imaging Department in Enam Medical College & Hospital, Savar, Dhaka in collaboration with the Department of Pathology of the same institution for FNAC correlation during October 2017 to November 2019. A total number of 50 patients with CLD with known hepatic mass, referred to the department were included in the study. Ultrasound was done with TOSHIBA using low frequency curvilinear probe of 3.5 MHz. USGguided aspirations was performed using 18G needle under full aseptic measure. USG findings were validated by histopathology reports. Analysis was done by SPSS 19.0. Results: Mean age of the study population was 58.6 ± 10.9 years, of whom 37(74%) were male and 13 (26%) were female. Mean size of the hepatic lesions was 4.7 ± 1.08 cm. The lesions were characterized as iso-, hypo- and hyperechoic as compared with hepatic parenchyma. Doppler study shows both central and peripheral vascularity. Compared with FNAC findings, accuracy of USG findings was determined. Sensitivity of USG in detection of HCC was 97.7%, specificity was 66.7%, and positive prediction value 95.6% and negative prediction value 80%. Conclusion: Conventional USG can be used as a screening method in patients with CLD having hepatic masses. However, further workup is required for definite diagnosis. J Enam Med Col 2020; 10(3): 153-158